(untitled) (Circe de clásicos y modernos, 2021)
The purpose of this essay is to point, review, and comment some intertextual strategies present in the poetic artifacts of Late Antiquity. We will specifically examine two passages of Dracontius poems, where the co-presence relationship between texts is ligated to certain anomalies in the metric cadence of verses. We will try to prove how, sometimes, the relegatio of textual variants to the critical apparatus has prevented to perceive phonic and semantically relevant poetic procedures.